2022
DOI: 10.1093/hr/uhab047
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and physiological analysis identifies a gene network module highly associated with brassinosteroid regulation in hybrid sweetgum tissues differing in the capability of somatic embryogenesis

Abstract: Somatic embryogenesis is a preferred method for large-scale production of forest trees due to its high propagation efficiency. In this study, hybrid sweetgum leaves with phase changes from mature to embryogenic state were selected as experimental material to study somatic embryo initiation. Embryogenicity ranged from high to low, i.e. from 45%, 25%, and 12.5% to 0, with the samples of embryogenic callus (EC), whiten leaf edge (WLI), whiten leaf (WLII), and green leaf (GL) respectively. High correlations existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Plant biotechnology, including tissue culture and genetic engineering, is gradually becoming an important breeding method to promote the improvement of pepper breeding. It is well known that several genes are involved in explant regeneration, including WOX , BBM , LEC , and WUS ( Zhao et al., 2022 ). Our results indicated that phytohormones play an important role in callus formation by regulating the expression of regeneration-related genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant biotechnology, including tissue culture and genetic engineering, is gradually becoming an important breeding method to promote the improvement of pepper breeding. It is well known that several genes are involved in explant regeneration, including WOX , BBM , LEC , and WUS ( Zhao et al., 2022 ). Our results indicated that phytohormones play an important role in callus formation by regulating the expression of regeneration-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Roles of WOX gene in the regeneration of pepper WOX family genes are important in a variety of processes, ranging from callus formation to organ development (Kim et al, 2018;Wang C. et al, 2021;Willoughby and Nimchuk, 2021). It was reported that WOX2 and WOX8/9 were involved in differentiation and somatic embryogenesis (Palovaara et al, 2010;Zhao et al, 2022). Based on the activity of WIND1, WOX13 was rapidly induced, which is a key regulator of callus formation (Ikeuchi et al, 2021).…”
Section: Analysis Of Starch and Sucrose Metabolism In Callus Inductionmentioning
confidence: 99%
“…With the development of bioinformatics technology, more and more new techniques are applied to analyze expression profile data. Differential gene analysis is the most classical analysis method, which plays an important role in this field of biomarkers by a series of statistical algorithms to find differential genes between different subgroups ( Liu et al, 2022 ; Zhao et al, 2022 ). WGCNA (weighted gene co-expression network analysis) is a topological network that can establish the linkage between gene modules and clinical traits, and the genes classified into the same module are all linked to selected clinical traits, which can then be used for subsequent analysis and experiments ( Nguyen et al, 2021 ; Ye et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brassinolide (BL) is the first discovered form of brassinosteroids (BRs) with the most bioactive properties and BRs play a crucial role in various aspects of plant growth and development, including cell growth and division, vascular bundle differentiation, cell redifferentiation, and growth under stress conditions ( Kim et al., 2009 ; Wei and Li, 2016 ; Bajguz et al., 2020 ; Kour et al., 2021 ; Singh et al., 2021 ; Manghwar et al., 2022 ). The regeneration and multiplication rate of in vitro cultured material could be improved by the addition of BRs to the medium for callus induction, somatic embryogenesis and embryogenic callus formation ( Singh et al., 2021 ); 4 types of hybrid sweetgum ( Liquidambar styraciflua × L. formosana ) with different embryogenic ties should be highly correlated with endogenous BRs; and BR concentrations of the samples should be positively correlated with the expression of genes associated with somatic embryos ( Zhao et al., 2022 ). In general, the general aspects of BRs have been studied in relative detail ( Singh et al., 2021 ; Chen et al., 2022 ), but Somatic embryogenesis (SE) involves the use of BRs, including their application effects and physiological and genetic mechanisms ( Kim and Moon, 2014 ; Chone et al., 2018 ; Zhao et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The regeneration and multiplication rate of in vitro cultured material could be improved by the addition of BRs to the medium for callus induction, somatic embryogenesis and embryogenic callus formation ( Singh et al., 2021 ); 4 types of hybrid sweetgum ( Liquidambar styraciflua × L. formosana ) with different embryogenic ties should be highly correlated with endogenous BRs; and BR concentrations of the samples should be positively correlated with the expression of genes associated with somatic embryos ( Zhao et al., 2022 ). In general, the general aspects of BRs have been studied in relative detail ( Singh et al., 2021 ; Chen et al., 2022 ), but Somatic embryogenesis (SE) involves the use of BRs, including their application effects and physiological and genetic mechanisms ( Kim and Moon, 2014 ; Chone et al., 2018 ; Zhao et al., 2022 ). Research has shown that BRs can regulate cell elongation by altering cell walls.…”
Section: Introductionmentioning
confidence: 99%